2021
DOI: 10.3390/ejihpe11030056
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Review of Research on International Students’ Mental Health: Science Mapping of the Literature from 1957 to 2020

Abstract: The mental health of university students is not only a predominant topic for psychology and education researchers but also a source of interest for policymakers and various stakeholders. Although there has been a lot of research on higher education students’ mental health, we have little understanding on the mental health of international students (MHIS). Despite their distinctive characteristics compared to native students, the mental health issues of international students only started receiving attention ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 106 publications
0
9
0
2
Order By: Relevance
“…Another considerable part focused on the impact of the pandemic from the point of view of business or the economy. Of these 489 reviews, 17 included some reference to stress [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] but none mentioned burnout. Likewise, 5 considered teachers [ 71 , 76 , 77 , 78 ], with 3 of them focusing on university teachers [ 71 , 77 , 78 , 79 , 80 ] and the other 2 on the use of learning through ICT [ 77 , 80 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another considerable part focused on the impact of the pandemic from the point of view of business or the economy. Of these 489 reviews, 17 included some reference to stress [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] but none mentioned burnout. Likewise, 5 considered teachers [ 71 , 76 , 77 , 78 ], with 3 of them focusing on university teachers [ 71 , 77 , 78 , 79 , 80 ] and the other 2 on the use of learning through ICT [ 77 , 80 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trắc lượng thư mục khoa học là một cách tiếp cận thực hiện nghiên cứu tổng quan. Phương pháp này sử dụng các phân tích thống kê mô tả đối với thông tin biên mục tài liệu, và được sử dụng rộng rãi ở nhiều lĩnh vực nhiên cứu khác nhau như là lĩnh vực nghiên cứu giáo dục đại học [2,10], giáo dục đặc biệt [1]. Trong lĩnh vực nghiên cứu khoa học thư viên, Nguyễn Hoàng Sơn [6] áp dụng các phương pháp thống kê để dự báo các xu hướng nghiên cứu chính về lĩnh vực thư viện số trên thế giới, kết quả cho thấy các công nghệ phục vụ cho thư viện thế hệ thứ ba sẽ là những chủ để nghiên cứu chủ đạo.…”
Section: Giới Thiệuunclassified
“…In fact, even before the pandemic, researchers already recognized that students studying abroad were prone to depression [2,3]. A recent analysis of study abroad articles published over the past 40 years identified growing concerns about students' mental health, particularly their relationship to language, including the different social and psychological difficulties [4]. This brought attention to the fact that while studying abroad, students may be prone to mental illnesses such as depression.…”
Section: Introductionmentioning
confidence: 99%